Pengembangan Media Pembelajaran Biologi dengan Aplikasi Play V berbasis Android - Sari, Riska; Safitri, Siti; Zulfa, Aniyatuz; Fahmi, Wahyunisa (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2023)
Biology material about viruses is often boring for some students, to solve this ptoblem, something interesting is needed in this research, with the development of the android Play V (Play and Learning Virus) application using the RnD and the ADDIE model, it succeeded in creating an interesting viral learning media with a validation of 85,25% to provide learning convenience for students in learning.